ANALISIS VARIASI SUBSTRAT AIR CUCIAN BERAS DAN KULIT PISANG MICROBIAL FUEL CELL TERHADAP ARUS LISTRIK - Andy Nugraha; Aji Nihin; Akhmad Syarief (Scientific Journal of Mechanical Engineering Kinematika, 2023)
Microbial fuel cell (MFC) is a technology that utilizes the biological activity of microorganisms to produce electricity from organic energy in the form of waste. Waste that is often encountered in everyday life, some of which are rice washing water and banana peel waste, which are easy to find and are often thrown away without being used, even though they contain organic content, which is a food source for microbes, which can later be converted into metabolic products from these microbes to produce electricity. Electricity within the microbial fuel cell (MFC) system. The microbial fuel cell in this research used a variety of substrates of rice washing water, banana peels and a mixed substrate of rice washing water and banana peels, as well as variations in incubation times of 3, 5 and 7 days. From the research that has been carried out, it is known that variations in the substrate mixture of rice washing water and banana peels (50%; 50%) have the greatest electric current, namely 0.262 mA at an incubation time of 5 days. In all substrate variations, there was an increase in electric current on the 3rd and 5th days of incubation and a decrease on the 7th